Modeling Human Zymogen Factor IX - Perera, Lalith; Darden, Thomas A.; Pedersen, Lee G. (Thrombosis and Haemostasis, 2001)
Modern theoretical techniques are employed to provide complete three dimensional structure for the zymogen and activated forms of human coagulation factors IX and IXa. These structures are fully calcium bound and equilibrated in an electrically neutral aqueous environment. The relationship of structure to mutational data is examined. We find that a substantial relative orientational change of the catalytic domain occurs on activation. Also, we find that the electrostatistically dipolar nature of the catalytic domain is substantially modified upon activation, with cleavage of the negatively charged activation peptide leaving behind a largely hydrophobic face in factor IXa. While the backbone atoms of the catalytic residues have little relative movement, nearby loops are found that do move. The presence or absence of these changes likely defines specificity.
Keywords: Factor IX; molecular dynamics simulations; serine protease; calcium binding